Analisis Penggunaan Media Sosial Dalam Motivasi Belajar PAI Kelas X Di Sekolah Menengah Kejuruan Negeri 9 Medan - Nafisa Risakotta; Bachtiar Siregar (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to analyze the influence of social media usage on the learning motivation of 10th-grade students at SMK Negeri 9 Medan. This research employs a descriptive qualitative approach. Both primary and secondary data sources were utilized. Data were collected through interviews, observations, and documentation. The data were analyzed using techniques of data reduction, data presentation, and conclusion drawing. The study, titled "The Impact of Social Media Usage on the Learning Motivation of 10th-Grade Students at SMK Negeri 9 Medan," reveals that social media significantly affects students' learning motivation. Some students experienced a decline in motivation due to excessive use of social media. However, when used wisely, social media can also play a positive role as a supportive tool in the learning process.